Role of PAX7 Gene rs766325 and rs4920520 Polymorphisms in the Etiology of Non-syndromic Cleft Lip and Palate: A Genetic Study - Khan, Mahamad Irfanulla; CS, Prashanth; Srinath, Narasimhamurty (Global Medical Genetics, 2022)
Non-syndromic cleft lip and palate (NSCLP) is one of the most common birth defects in humans with an overall prevalence of ∼1 in 700 live births around the world. The etiology of NSCLP is complex involving multiple genes, environmental factors, and gene-to-gene interactions. Several genome-wide associations (GWA) studies have shown the association of the paired box 7 (PAX7) gene in the etiology of cleft lip and palate in different populations worldwide. However, there are no reported studies on the association between the rs766325 and rs4920520 polymorphisms and the risk of developing NSCLP in the Indian population. Hence, the present study aimed to test for the probable association between rs766325 and rs4920520 polymorphisms among NSCLP Indian population using a case-parent trio design. Forty case-parent trios were selected from the cleft lip and palate center based on the inclusion and exclusion criteria. Genomic DNA was isolated from the cases and their parents. The rs766325 and rs4920520 polymorphisms of the PAX7 gene were analyzed for their association using the MassARRAY analysis. The statistical analysis was done using the PLINK software. The rs766325 and rs4920520 polymorphisms were tested for the Hardy–Weinberg equilibrium. None of the polymorphisms showed any statistical significance. Hence, the rs766325 and rs4920520 polymorphisms of the PAX7 gene were found to be not associated with NSCLP in the Indian case-parent trios.
Keywords: non-syndromic; cleft lip and palate; PAX7; DNA extraction; genotyping